Antibacterial Efficacy of Hiora: An Ayurvedic Mouthwash in Children - Saha, Sonali; Kalita, Kongkana; Dhinsa, Kavita; Arora, Deval Kumar; Godhi, Brinda Suhas; Doddawad, Vidya Gowdappa (Drug Research, 2024)
Background Mouthwashes, as a form of antimicrobial delivery system, rank among the safest and most effective vehicles, particularly in the case of young children. This is attributed to their ability to distribute therapeutic components across all accessible oral surfaces, including interproximal areas.Objective To evaluate the antibacterial efficacy of recently introduced Ayurvedic (Hiora) and triclosan-based mouthwashes among children.Materials and Methods A total of 45 healthy children aged 10–15 years were randomly assigned to three groups: Herbal mouthwash (Hiora), triclosan-based mouthwash (Kidodent), and normal saline as the control group. Saliva samples were collected pre-rinse, 2 minutes, 30 minutes, and 60 minutes post-rinsing with the study mouthwashes. These samples were then inoculated onto Petri dishes containing blood agar culture media, followed by incubation under both aerobic and anaerobic conditions at 37°C for 48 hours. The resulting bacterial colonies of Streptococcus spp. and Lactobacillus spp. were counted (CFU/ml x 105). Statistical analysis, including ANOVA, Newman Keul’s Post-hoc test, and a two-tailed ‘t’ test, was conducted to determine the significance of the results.Results The Ayurvedic Hiora mouthwash demonstrated the most substantial reduction in salivary bacterial colony counts of Streptococcus spp. and Lactobacillus spp. with statistically significant results (p<0.01).Conclusion The Ayurvedic Hiora mouthwash exhibited the highest antibacterial effectiveness, followed by the triclosan-based mouthwash in decreasing order, with saline showing the least efficacy.
Keywords: antibacterial agent; prevention mouthrinse; ayurvedic; traditional; pediatrics